1995
DOI: 10.1136/thx.50.10.1080
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effects of plasma exchange and pyridostigmine on respiratory muscle strength and breathing pattern in patients with myasthenia gravis.

Abstract: Background-Pyridostigmine, an acetylcholinesterase antagonist, is useful in improving respiratory function in patients with myasthenia gravis. More recently, plasma exchange has been employed in myasthenia gravis because it acts presumably by removal of circulating antibodies against acetylcholine receptors. Surprisingly, comparative data on the effects of pyridostigmine and plasma exchange on lung volumes, respiratory muscle strength, and ventilatory control system in patients with myasthenia gravis are lacki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0
7

Year Published

1999
1999
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 24 publications
0
21
0
7
Order By: Relevance
“…This study found improvement in respiratory measures, including a decrease in functional residual capacity and residual volume and an increase in forced expiratory volume in 1 second, maximum inspiratory pressure, and maximum expiratory pressure ( p Ͻ 0.05) in the plasmapheresis cohort. 16 A retrospective Class III study compared 19 patients treated with a single session of plasmapheresis prior to thymectomy vs 32 patients treated with thymectomy alone. The patients treated with plasmapheresis had less occurrence of crisis in the following month ( p ϭ 0.0724) and year ( p ϭ 0.049) and a greater remission rate at 5-7 years postoperatively.…”
mentioning
confidence: 99%
“…This study found improvement in respiratory measures, including a decrease in functional residual capacity and residual volume and an increase in forced expiratory volume in 1 second, maximum inspiratory pressure, and maximum expiratory pressure ( p Ͻ 0.05) in the plasmapheresis cohort. 16 A retrospective Class III study compared 19 patients treated with a single session of plasmapheresis prior to thymectomy vs 32 patients treated with thymectomy alone. The patients treated with plasmapheresis had less occurrence of crisis in the following month ( p ϭ 0.0724) and year ( p ϭ 0.049) and a greater remission rate at 5-7 years postoperatively.…”
mentioning
confidence: 99%
“…A useful study from Florence compared improvement in breathing pattern (vital capacity) in MG by treatment by pyridostigmine (VC +10%) vs. PEX (VC +14%) and MIP (Mean inspiratory pressure) increases of 18 and 26%, respectively [60]. A French report of failure to wean from a respirator a typical MG patient under 2 years CS treatment with 4 PEX and Azathioprine showed steroid-induced myopathy by histology along with peripheral and diaphragm EMG [61].…”
Section: Discussionmentioning
confidence: 97%
“…Use of plasmapheresis in the treatment modality of MG was reported as early as 1976 by pinching et al, 5 Plasmapheresis is known to improve respiratory function when compared with pyridostigmine and is found to be useful in ventilator dependency in a non randomized trial of nine patients. 6 The use of plasmapheresis to control MC or in preoperative preparation of thymectomy remains inadequately studied. 7 In our case clinical course was complicated by autonomic instability, a rare but recognized manifestation of MG.…”
Section: Discussionmentioning
confidence: 99%